2016
DOI: 10.1021/acs.energyfuels.6b01433
|View full text |Cite
|
Sign up to set email alerts
|

Mechanically Stable Mixed Metal Oxide of Cu and Mn as Oxygen Carrier for Chemical Looping Syngas Combustion

Abstract: Chemical looping combustion possesses an inherent advantage of separation of CO2 from the carbon based fuels including thermal power plants that would offer effective mitigation of CO2 emissions through carbon capture and sequestration. In this study, a stable and regenerative mixed transition metal oxide of Cu and Mn (CuMn2O4) is synthesized through coprecipitation method and tested for multicycle performance for the oxidation of syngas as fuel. It was observed that 90% of the oxygen carrying capacity of CuMn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 25 publications
0
13
0
Order By: Relevance
“…Finally, Figure shows the surface morphology of the Cu–Mn composite oxygen carrier before and after consecutive redox cycles. After the reaction of copper and manganese oxides, the structure of the OC surface is modified, and the surface is smooth . Both the fresh and cycled samples present a porous structure that provides channels for oxygen diffusion, which is important for the redox reaction rates.…”
Section: Resultsmentioning
confidence: 99%
“…Finally, Figure shows the surface morphology of the Cu–Mn composite oxygen carrier before and after consecutive redox cycles. After the reaction of copper and manganese oxides, the structure of the OC surface is modified, and the surface is smooth . Both the fresh and cycled samples present a porous structure that provides channels for oxygen diffusion, which is important for the redox reaction rates.…”
Section: Resultsmentioning
confidence: 99%
“…Researchers found that the initial oxygen-releasing temperatures of Cu–Mn oxygen carriers were 620–850 °C and the oxygen uptake of this composite oxygen carrier was significantly larger than the oxygen uptake of a Mn-based oxygen carrier. The initial oxygen-releasing temperature is about 200 °C lower than that of a Cu/Zr oxygen carrier. Thus, a copper and manganese composite oxide can be a good candidate for low-temperature CLAS. However, systematic and detailed studies on the properties and, particularly, reaction kinetics of composite Cu–Mn oxygen carriers are still scarce in the literature.…”
Section: Introductionmentioning
confidence: 99%
“…as low-cost, environmentally benign oxygen carriers are developed recently that can be used as alternative to the currently available oxygen carriers for CLC [11][12][13][14][15]. These mixed oxides form MnO as one of the products after chemical looping combustion reaction using methane, syngas, etc.…”
Section: Introductionmentioning
confidence: 99%
“…These mixed oxides form MnO as one of the products after chemical looping combustion reaction using methane, syngas, etc. and it provides the structural stability to their reduced co-products, which facilitates the regeneration of these oxygen carriers upon heating in air (self-supported oxygen carrier) [11][12][13]. The developed oxygen carrier showed enhanced CLC activity for methane and syngas combustion in terms of multi-cycle performance, stability, CO 2 -selectivity, etc.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation